Egyptomania : our three thousand year obsession with the land of the pharaohs - Brier, Bob. (Palgrave Macmillan, 2013)
Presents the history of the West's obsession with ancient Egyptian art and culture, from the time of the Romans, to the campaigns of Napolean Bonaparte, the discovery Tutankhamen's tomb, and the popular culture of today.